The influence of the trajectory of obesity indicators on the age of pubertal onset and pubertal tempo in girls: A longitudinal study in Chongqing, China - Xi, Xuan; Wu, Di; Wu, Wenyi; Zhou, Yuanke; Zhang, Qin; Wang, Yujie; Wang, Hong; Liu, Qin (Frontiers in Public Health, 2023)
Objective: To explore the influence of the trajectory of obesity indicators on the onset age of different pubertal development characteristics and pubertal tempo among girls. Methods: Our longitudinal cohort study recruited 734 girls at baseline in May 2014 and followed at 6 months intervals in a district of Chongqing. Data were available from baseline to the 14th follow-up with full record of height, weight, waist circumference (WC), breast development, pubic hair and armpit hair development and the age of menarche. The Group-based Trajectory Model (GBTM) was fitted for optimum trajectory of the body mass index (BMI), WC and waist-to-height ratio (WHtR) of girls before the pubertal onset and menarche. The ANOVA and multiple linear regression model were conducted to analyze the influence of the trajectory of obesity indicators on the onset age of different pubertal development characteristics and pubertal tempo in girls. Results: Compared with the healthy (gradual BMI increase) group before pubertal onset, the overweight (persistent BMI increase) group has an earlier onset age of breast development (B:-0.331, 95%CI:-0.515, -0.147) and pubic hair development (B:-0.341, 95%CI:-0.546, -0.136). The B2-B5 development time was shorter in girls with overweight (persistent BMI increase) group (B:-0.568, 95%CI:-0.831, -0.305) and obese (rapid BMI increase) group (B:-0.328, 95%CI:-0.524, -0.132). The age of menarche was earlier and the B2-B5 development time was shorter in girls with overweight (persistent BMI increase) than healthy (gradual BMI increase) before menarche (B:-0.276, 95%CI:-0.406, -0.146; B:-0.263, 95%CI:-0.403, -0.123). Girls with high WC (rapid WC increase) before menarche had earlier age of menarche than normal WC (gradual WC increase) (B:-0.154, 95%CI:-0.301, -0.006), and the B2-B5 development time was shorter in girls with overweight (gradual WHtR increase)group than healthy (persistent WHtR increase)(B:-0.278, 95%CI:-0.529, -0.027) group. Conclusions: Among girls, overweight and obesity (BMI scale) before pubertal onset can not only influence pubertal onset age, but also accelerate B2-B5 pubertal tempo. Overweight (BMI scale) and high WC before menarche also have an impact on age of menarche. Overweight (WHtR scale) before menarche is significantly associated with B2-B5 pubertal tempo.